Counselors' education in complex contexts with special reference to Latin America - Gavilán, Mirta Graciela (2007)
This paper makes reference to the importance lying, at present, on the professional education of counselors. It goes through the history of the different pre-scientific and scientific stages of counseling, and it points out the main representatives in Latin America . It also shows the current state of the specialization, taking as an antecedent some in-depth, widely encompassing research carried out in the European Union in this area. Coincidences and differences are exposed here in terms of professional profiles, university degrees, institutional dependence, up-dating processes and modes of intervention. The current state of postgraduate studies at university is also touched upon, and the different proposals for further education in Latin America are analyzed as well as their dependence upon an undergraduate degree in Psychology, Educational Sciences or Psycho-pedagogy. Finally, this paper places counseling within the complexity and the need to provide all-encompassing and integrative answers which require a wide and deep enough education so as to answer all these issues and problems.